Mobile applications for weather and climate information: their use and potential for smallholder farmers - Caine, A; Dorward, P.; Clarkson, G.; Evans, N; Canales, C.; Stern, D.; Stern, R. (2015)
Mobile phones are increasingly being used to provide smallholder farmers with agricultural and related information. There is currently great interest in their scope to communicate climate and weather information. Farmers consistently identify demand for weather information and whilst ICTs may be one way of delivering this at scale there are concerns that this should not be seen as a panacea. At a time when there have been a range of initiatives and projects that have been implemented this paper seeks to draw lessons and identify key considerations to inform the development of future mobile applications to provide climate services to smallholder farmers. A literature review, interviews with key informants and experts and 15 case study reviews were conducted. This focused principally on Sub Saharan Africa but included some examples from India. Despite numerous initiatives few have developed fully beyond the pilot stage and few have been evaluated. Some of the provision to date has been of questionable value to farmers. A key observation is that relatively little attention has been paid in design, to the needs for and use of both the information and technology by farmers, and few attempts made to differentiate provision according to gender and other demographic variables. Other factors contributing to success included communications approaches, which are interactive and/or involve trusted intermediaries who can add context to and help interpret more complex information. Providing weather information alongside other services as ‘bundles’ and in conjunction with complementary communications approaches appears to work well. An important challenge is how to meet farmers’ needs for location specific, timely and relevant information in economically sustainable ways. More widely there are challenges in achieving successful business models and potential conflicts between initiatives driven by mobile network operators and public goals. The study identified areas of considerable potential which include: the use of increasingly available mobile data connections to ensure locally relevant content is available to farmers in timely fashion (including both historical climate information and forecasts); development of participatory decision making tools to enable farmers to interpret information for their own contexts and consider implications and management options; use of visual applications and participatory video on mobile devices to enhance learning and advisory services for farmers; the potential for increased feedback between farmers and service providers as well as increased knowledge sharing between farmers provided by the use of social media.